RELEVANSI FITRAH MANUSIA DENGAN PENDIDIKAN TAFSIR-HADIS TARBAWI - Faridah, Faridah; Karimah, Ummah (Asosiasi Dosen PTKIS Indonesia, 2024)
: Tawhid is the core that will be targeted by Islamic education, so that in the context of fitrah it is a matter of righteousness and righteousness that is tawhid. However, the jawavbah has never been completed, let alone completed in one meeting or several stages of study, until now the problem continues and inspires the minds and hearts of Indonesia Muslims in particular, which sometimes leads to unrest, one of the questions is where to take Islamic education? This paper examines education in the style of tafsir hadith tarbawi, so that it is certain to provide a solution in the context of problem solving for the existence of Islamic educational relations and their nature and their problems, or at least provide an overview that can be used as good news. So it is hoped that a little or a lot will participate in easing the unrest. The discussion will focus on two essential things, namely: the meaning and types of fitrah of education as fitrah mukammilah whose elaboration is carried out sequentially in the following sections.